A study of the job description of library personnel of the College of Arts and Letters Library and the College of Social Sciences and Philosophy Library of the University of the Philippines Diliman - Cruz, Luis Ezra D.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The study aims to examine the job descriptions of personnel of library units in University of the Philippines Diliman. It intends to present the duties listed in the respective job description of the library staff members and see if it matches with the duties they perform. The two library units included in the study are the College of Arts and Letters Library and the College of Social Sciences and Philosophy Library in UP Diliman.
A total of 26 library workers from the two libraries served as the respondents. Job descriptions and specific performance targets of each staff was culled from the library unit heads to determine the assigned tasks and the actual tasks performed by the staff. Data analysis was done to particularly look into the similarities and differences in the duties listed in the job descriptions and the actual tasks performed by the staff. An interview was also done to supplement the data gathered from the two documents.
The pertinent data obtained from the data analysis and supplemental interviews revealed that: (a) 76 of the respondents of the study are staff members of the College of Social Sciences and Philosophy Library; (b) There are thirteen support staff (52) and twelve (48) professional staff in the two libraries; (c) Professional staff members of both the College of Arts and Letters Library (CAL) and the College of Social Sciences and Philosophy (CSSP) Library perform the tasks assigned to them via their respective job descriptions but also tend to perform duties not listed in their job descriptions; (d) the professional staff of the CAL Library tend to perform duties of library staff occupying other positions, primarily tasks of the support staff members and the professional staff of the CSSP Library tends to perform duties of other professional staff occupying other positions; (e) tasks listed in the job description of the support staff members of both the College of Arts and Letters Library and the College of Social Sciences and Philosophy Library fully correspond with the duties they execute thus they only perform duties given to them.
Recommendations presented are: (a) updating the job description of the library personnel to ensure that obsolete tasks are discarded and emerging duties are added; (b) examining the job descriptions of each staff to ensure that the duties are commensurate to the position of the staff; (c) employing additional support staff in the College of Arts and Letters Library; (d) assigning the duties to the right personnel strictly according to the job descriptions of the support staff; and (e) further studies regarding job descriptions should be done in the other library units in UP Diliman as well as in other types of libraries.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines College of Social Sciences and Philosophy; University of the Philippines College of Arts and Letters Library; Employees -- Job descriptions